The Influence of Green Human Resource Management on Enhancing Green Innovative Work Behavior: The Mediating Role of Green Work Engagement - Anang Dirjo (Jurnal Manajemen Sains dan Organisasi, 2025)
Objective – The purpose of the current study was to examine the effect of Green Human Resource Management (GHRM) on Green Innovative Work Behavior (GIWB), with the mediating effect of Green Work Engagement (GWE). Using multi-industry data allows for increased generalizability of the findings. This study contributes to the understanding of the psychological underpinnings of the relationship between GHRM and sustainable innovation in organizational settings. Design/Methodology/Approach – The research uses a quantitative approach with data collection through questionnaires from respondents in various organizations that implement GHRM practices. Data analysis was conducted using the Partial Least Squares Path Modeling (PLS-SEM) method to test the relationships between variables. Findings – The research results that GHRM practices such as recruitment, training, and green performance management significantly enhance green work engagement. Furthermore, green work engagement positively mediates the relationship between GHRM and green innovative work behavior. In other words, GHRM encourages employees to become more emotionally and cognitively engaged in environmentally oriented work, which in turn enhances green innovation in the workplace. Implications – The implementation of GHRM is effective in building an organizational culture that supports innovation and environmental responsibility among employees. The practical implication is that organizations aiming to enhance green performance and competitiveness must integrate environmentally conscious HRM practices and actively promote green work engagement.